2017
DOI: 10.1002/adfm.201705091
|View full text |Cite
|
Sign up to set email alerts
|

Directional and Continuous Transport of Gas Bubbles on Superaerophilic Geometry‐Gradient Surfaces in Aqueous Environments

Abstract: Due to the direct and sufficient contacting with the aqueous environment, the directional and continuous transport of gas bubbles on open surface without energy input will advance a variety of applications in heat transfer, selective aeration, water electrolysis, etc. Unfortunately, the behaviors of gas bubbles in aqueous environment are mainly dominated by the buoyancy moving gas bubbles upward, resulting in their difficult manipulation. Therefore, realizing the directional and continuous transport of gas bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 43 publications
1
92
0
Order By: Relevance
“…The surface tension and later buoyancy are two crucial factors to drive the rapid evolution of bubbles spreading in three typical stages and further confirmed that the characteristic spreading time (10 ms) of the bubble on a superaerophilic surface (SALS) is much shorter than that in other plates, which agrees well with the results of Wang et al [18]. Moreover, Ma et al [19] combined the geometry-gradient structure with the spreading of bubbles on the upper SALS to manipulate the directional transport of bubbles without energy input.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The surface tension and later buoyancy are two crucial factors to drive the rapid evolution of bubbles spreading in three typical stages and further confirmed that the characteristic spreading time (10 ms) of the bubble on a superaerophilic surface (SALS) is much shorter than that in other plates, which agrees well with the results of Wang et al [18]. Moreover, Ma et al [19] combined the geometry-gradient structure with the spreading of bubbles on the upper SALS to manipulate the directional transport of bubbles without energy input.…”
Section: Introductionsupporting
confidence: 87%
“…This migration capacity of the ruptured bubbles provides a potential solution for the horizontally directional transport of the bubble in aqueous environments. Ma et al recently proposed this interesting topic [19], using the geometry gradient of the SALS to transport the bubble horizontally. Once the two sub-bubble humps established as a result of the interface necking before rupture, a high degree of symmetry in the two ruptured bubbles, including the migration velocity and bubble geometry, can be found during this whole dynamical process ( Figures 5 and 7).…”
Section: Bubble Rupture On the Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, numerous efforts have concentrated on directional manipulation of underwater bubbles. To achieve gradient wettability at the surface of materials, many researchers have developed a series of gradient geometries, such as ratchets, cones, trapezia, and cylinders, and gradient surface free energy, for underwater gas bubbles transport. In addition, a reversible wettability‐switching surface has been fabricated to capture or repel gas bubbles in water by selective switching between underwater superaerophobicity and aerophilicity .…”
Section: Introductionmentioning
confidence: 99%
“…The manipulation of underwater bubbles is significant in a fluid system due to its large-scale applications, such as electrocatalytic gas evolution reactions, wastewater remediation, and solar energy harvesting [1][2][3][4][5][6][7][8][9][10][11]. Meanwhile, the bubbles play an important role in nature.…”
Section: Introductionmentioning
confidence: 99%